Adoção de blockchain para sustentabilidade em cadeias de suprimentos: um estudo de caso no setor têxtil - Silva, Alexandre Lacerda e (2021)
This paper seeks to investigate how a technology as promising as blockchain can contribute to better sustainable management of supply chains. Blockchain is part of a set of modern information technologies that include, among others, Machine Learning, and Internet of Things (IoT). These technologies support the digital transformation experienced by different sectors of the economy in different processes, supply chains are no exception to this rule. In a world of globalized chains, digital technologies are increasingly vital for the management of inputs, whether in a conventional or sustainable way. Blockchain started out as the technology of cryptocurrencies and soon began to be employed in a myriad of applications, including supply chain management. Going further to what used to be a hype, blockchain came to be seen pragmatically by companies and promises to deliver more scale in sustainability practices, especially in traceability and transparency. In order to answer the research question, a qualitative research of a single case was elaborated, complemented by insights from practitioners in companies in Brazil and abroad. The work identified that the attributes of blockchain found in the literature review referred to the reality of the companies, that blockchain is a viable, scalable technology and that delivers what it promises. However, the realization of the maximum potential of technology for Sustainability has a lot to do with the commitment that companies have to sustainability, with pressure from society and with governance in supply chains. In combining these factors with the objective of taking Sustainability practices to a higher level, technology can make an important contribution to this.